CYBER SECURITY AND SCHOOL MANAGEMENT IN NIGERIA - Niyi Jacob Ogunode; Florence Onyemowo Akpakwu; Donatus Peter Ochai (PT. Antis International Publisher, 2025)
Objective: This study examines the significance of effective cybersecurity management in Nigerian schools and its implications for data protection, legal compliance, and educational stability. Method: A qualitative analysis was conducted, reviewing relevant policies, existing cybersecurity frameworks, and their application within the Nigerian education sector. Results: The findings indicate that adopting cybersecurity measures enhances the protection of sensitive school data, ensures compliance with the Child Rights Act and record-keeping regulations, fosters a stable learning environment, safeguards intellectual property, supports remote and virtual learning, and facilitates informed decision-making in school management. Novelty: This study highlights the critical role of cybersecurity in maintaining the integrity and security of educational institutions in Nigeria, emphasizing the necessity for structured policies and training programs. It underscores the need for federal, state, and local education authorities to implement comprehensive cybersecurity strategies and provide professional development for educators and school administrators. Additionally, it advocates for stronger stakeholder engagement in cybersecurity initiatives to ensure effective implementation and sustainability.